Prevalence of burnout and its determinants among Indonesian nurses: a multicentre study - I. Gede Juanamasta; Yupin Aungsuroch; Joko Gunawan; Michael Joseph Dino; Rapin Polsook (Scientific Reports)
Abstract Frontline health workers face a significant issue concerning mental health, particularly stress and burnout. Nurses, being among them, grapple with this problem. The study aims to investigate the prevalence and determinants of burnout among nurses. A multicenter cross-sectional study was conducted across twenty two hospitals. A total of nine hundred nurses participated through convenience sampling. Burnout was measured using a single-measurement approach. Both individual and unit-related factors were examined. Over half of the nurses experienced stress, while 7.3% had symptoms of exhaustion. One in every hundred nurses faced a high likelihood of experiencing complete burnout. Job satisfaction, basic salary, motivation, age, incentives, competence, extra responsibilities, and knowledge of quality emerged as significant predictors of burnout. Addressing burnout among nurses requires hospitals to improve job satisfaction, revisit salaries, and foster supportive environments with incentives. Tailored training and ongoing support are crucial for resilience. Prioritizing these strategies is vital for nurses' well-being and sustainable healthcare delivery.